Comparative efficacy and safety of antivascular endothelial growth factors for central retinal vein occlusion: A protocol for systematic review and network meta-analysis. Issue 52 (30th December 2021) - Liu, Zhigao; Wang, Shuya; Ma, Aihua; Zhao, Bojun
Abstract: Background: Central retinal vein occlusion (CRVO) is one of the most common retinal vascular diseases, which is closely related to systemic diseases like hypertension, diabetes and arteriosclerosis. Due of its blinding, it will seriously reduce the quality of life. Macular edema (ME) caused by CRVO is one of the serious complications of visual impairment. We found that the severity of ME in CRVO was positively associated with vascular endothelial growth factor (VEGF) in the anterior chamber. With the accelerated pace of modern life and the changed dietary structure, the incidence of this disease will continue to rise. Therefore, it is of great practical significance to seek effective treatment methods. Intraocular injection of anti-VEGF can effectively alleviate ME and improve visual acuity, showing excellent clinical application prospects. In recent years, there have been some new understandings and advances on the etiology and treatment methods of the present disease, such as the deepening into the molecular biology and gene level. Clinical studies on the efficacy of the disease have emerging. Therefore, a network meta-analysis (NMA) of anti-VEGF treatment for CRVO is particularly necessary to systematically compare its efficacy. Methods: The two reviewers will comprehensively retrieved electronic databases such as PubMed, The Cochrane Library, Wanfang database, Web of Science, Chinese Scientifific Journals Database, EMBASE, China National Knowledge Infrastructure, and China BioMedical Literature. A randomized controlled trial for CRVO against VEGF between January 2010 and June 2021 was included according to the relevant content of the study. In addition, 2 researchers will screen the literature to assess the risk bias for the included articles. We will evaluate the collected evidence and data using a Bayesian NMA method, and analyzed it with STATA and WinBUGS software. Results: Anti-VEGF is one of the effective methods for ME in CRVO patients, accordingly, this study will evaluate its efficacy and safety using a Bayesian NMA system. Conclusion: This study can provide an effective rationale for the clinical application of anti-VEGF for CRVO, contribute to the treatment of CRVO and patient condition rehabilitation in clinical work. Ethics and dissemination: Do not require. INPLASY registration number: INPLASY2021110073.